The Influence Of Service Quality On Patient Satisfaction At Rsia Aisyiyah Samarinda, East Kalimantan - Jubaidi Jubaidi; Audi Aisyah Salsabila; Audya Shoffy Hadi Lestari; Aura Dira Larassati (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
Patient satisfaction is one indicator of the quality of the services provided by the hospital. Service quality can be reflected through five dimensions of service quality, namely tangible, reliability, responsiveness, assurance, and empathy. If the services provided by the hospital to patients are felt to be in line with expectations or even exceed expectations, then patient satisfaction can be said to be achieved. Patient satisfaction is part of the sustainability of the hospital itself, so the aim of this research is to assess the influence of service quality on patient satisfaction at RSIA Aisyiyah Samarinda, East Kalimantan. The data analyzed came from questionnaires distributed to 100 patients. Data analysis used multiple linear regression analysis using the SPSS 22 program. The results showed that simultaneously all independent variables had a significant effect on patient satisfaction, while partially only tangible and reliability variables had a significant effect on patient satisfaction, while responsiveness, assurance and empathy partially does not have a significant effect on patient satisfaction at RSIA Aisyiyah.